An exon-biased biophysical approach and NMR spectroscopy define the secondary structure of a conserved helical element within the HOTAIR long non-coding RNA - Abzhanova, Ainur; Hirschi, Alexander; Reiter, Nicholas J. (Journal of structural biology, 2021)
[Display omitted] •-Structure determination is challenging for lncRNAs that contain multiple splice isoforms.•-An exon-biased biophysical approach that includes NMR and chemical probing was developed to identify homogenous conformations within the exons of HOTAIR.•-HOTAIR exon 4 contains a well-defined helical conformation, previously identified as a conserved RNA structure.•-Combined NMR with chemical probing methods provide accuracy in the secondary structure determination of large RNA molecules. HOTAIR is a large, multi-exon spliced non-coding RNA proposed to function as a molecular scaffold and competes with chromatin to bind to histone modification enzymes. Previous sequence analysis and biochemical experiments identified potential conserved regions and characterized the full length HOTAIR secondary structure. Here, we examine the thermodynamic folding properties and structural propensity of the individual exonic regions of HOTAIR using an array of biophysical methods and NMR spectroscopy. We demonstrate that different exons of HOTAIR contain variable degrees of heterogeneity, and identify one exonic region, exon 4, that adopts a stable and compact fold under low magnesium concentrations. Close agreement of NMR spectroscopy and chemical probing unambiguously confirm conserved base pair interactions within the structural element, termed helix 10 of exon 4, located within domain I of human HOTAIR. This combined exon-biased and integrated biophysical approach introduces a new strategy to examine conformational heterogeneity in lncRNAs and emphasizes NMR as a key method to validate base pair interactions and corroborate large RNA secondary structures.